An Analysis of Primary and Secondary Slang Used in The Movie “Plane” by Jean François Richet - Wirajaya, I Wayan Indiana; Nova Winarta, Ida Bagus Gde (Humanis; Vol 28 No 3 (2024)DO - 10.24843/JH.2024.v28.i03.p03, 2024)
This study entitled “ An Analysis of Primary Slang and Secondary Slang Used in The Movie “Plane” by Jean- Francois Richet. T his research aimed to explore the utilization of primary and secondary slang in the movie titled "Plane," directed by Jean-François Richet.   To collect the data, a structured approach involving qualitative descriptive methods. Additionally, the study utilized Chapman  (2007)  as the theoretical framework. The analysis showed that secondary slang words were more common in the movie, with 16  (73%)  instances, compared to 6 (27%) instances of primary slang.   In conclusion, this research emphasized the importance of primary and secondary slang in the movie , showcasing their role in character interactions and narrative authenticity. The study of the movie "Plane" and the use of Chapman's slang language theory enhanced our understanding of language's contribution to cinematic storytelling.